2016
DOI: 10.1109/tsg.2015.2456107
|View full text |Cite
|
Sign up to set email alerts
|

Bilevel Model for Analyzing Coordinated Cyber-Physical Attacks on Power Systems

Abstract: This paper analyzes a coordinated cyber-physical attack on power systems, which could lead to undetectable line outages. Coordinated with physical attacks that cause line outages, the two-step cyberattacks comprising topology preserving and load redistribution attacks could mask and potentially exasperate outages to trigger cascading failures. These coordinated cyber-physical attacks are analyzed in a proposed bilevel model, which aims at identifying the most damaging and undetectable physical attacks constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(105 citation statements)
references
References 29 publications
0
105
0
Order By: Relevance
“…In particular, FDI attacks against power grid state estimation have been extensively studied [10], [11], [12]. While FDI attacks affect only the sensor measurements that are conveyed to the control center (and hence consist only of a cyber attack), recent research [3], [4], [5], [6] has studied CCPAs attacks, which as noted above consist of both cyber and physical components. CCPAs were first proposed in [3] based on disconnecting a set of transmission lines and blocking sensor measurements from the attacked area.…”
Section: Prior Workmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, FDI attacks against power grid state estimation have been extensively studied [10], [11], [12]. While FDI attacks affect only the sensor measurements that are conveyed to the control center (and hence consist only of a cyber attack), recent research [3], [4], [5], [6] has studied CCPAs attacks, which as noted above consist of both cyber and physical components. CCPAs were first proposed in [3] based on disconnecting a set of transmission lines and blocking sensor measurements from the attacked area.…”
Section: Prior Workmentioning
confidence: 99%
“…Moreover, under some conditions, it was shown that the operator can recover the phase angles and detect the physical attack using information from outside the attacked zone [3]. On the other hand, [4], [5] and [6] proposed the design of cyber attacks that can completely mask the effects of the physical attack under different assumptions about the attacker's knowledge. Further, [4], [5] and [6] have also investigated defense against CCPAs relying on a subset of protected measurements, which however is vulnerable (see Section I).…”
Section: Prior Workmentioning
confidence: 99%
See 3 more Smart Citations